Efeito do consumo de dietas elaboradas com mortadelas defumadas e não defumadas sob o perfil lipídico e aspectos histopatológicos do fígado e do cólon intestinal de ratos machos. - Barbosa, Mayara Queiroga (2011)
The highest intake of processed meat products in relation to red meat may increase the risk of colon cancer incidence and / or rectum and prostate. Despite ample evidence of this relationship further research is needed to indicate which foods are involved with this risk and to help clarify the mechanisms of the relationship between dietary com-ponents and the development of these diseases. Aiming to collaborate with more in-formation about this important topic, this research was conducted with the purpose of, from the experimental animal model to evaluate the effect of consuming diets contain-ing bologna and smoked not smoked on the biochemical and histopathological aspects of liver cells and intestinal colon of rats (Wistar) male. A total of 30 rats with 90 days of life divided into three groups. The Control group received a standard diet with case-in, the group consuming traditional diet made with Mortadella Bologna traditional source of protein that was supplemented with casein and the third group ate a diet de-signed with smoked Mortadella Bologna as a source of protein that was supplemented with casein (Smoked group), experimental diets were offered daily for a period of 90 days. Were examined analysis of the composition and identification of fatty acids of bologna. During the trial, held weekly assessment of weekly intake and weight gain of animals. After 90 days the animals were weighed and anesthetized to collect blood for analysis of plasma lipid fractions. Excision was performed, cleaning and weighing of the liver, spleen and visceral fat and performed histopathological analysis of liver and intestinal colon. The traditional sausage and smoked sausage contained respectively 15.27% ± 1.35 and 15.85 ± 1.89% protein, 26.19% ± 0.43 and 25.38 ± 0.272% fat, 2.46% 3.075 ± 0.049 and ± 0.45% carbohydrate, 2.65% ± 0.507 and 3.085 ± 0.45% of ash. The proportion of monounsaturated fatty acids: polyunsaturated: saturated (M: P: S) detected was 2.7: 1: 2.2 and 2.6 in the traditional bologna: 1: 2.1 in smoked sau-sage, not showing the recommended proportion . The consumption of diets showed significant differences between groups and between weeks. The body weight of the animals and traditional smoked increased steadily with time and the control group showed oscillations. The levels of plasma lipid fractions were higher in group smoked. It is concluded that the quality and the proportion of fatty acids monounsaturated: po-lyunsaturated: saturated (M: P: S) present in both types of mortadella contributed sig-nificantly to these results and that although the fatty acid composition are similar, the animals consumed diet containing smoked sausage showed greater imbalance in the lipid profile, which may have been caused by increased food intake. Regarding the histopathological analysis of liver, smoked group was observed higher concentration of mononuclear cells within hepatic portal, which may have been caused by chemical substances present in sausage smoked by the deposition of the smoke settles